Sub topics
-Differentiation by first principles
-Techniques of differentiation
-First and second derivatives
-Implicit differentiation
-Application of differentiation
DIFFERENTIATION BY FIRST PRINCIPLE
The concept of differentiation
The gradient of a curve at a given point is defined as the gradient of the tangent to the curve at that point and is given by the change of y with respect to x.
As B A
The gradient of the chord AB
The gradient of a tangent AT at point A
Or
Line gradient of chord AB = gradient of tangent AT
Example
Find the gradient of the curve
y = 2x2+ 5
Solution
At point Q
y + y = 2 [x+
x]2 +5
=2 [x2+ 2x x+
x2] +5
= 2x2 +4x x + 2
x2 +5…………. (i)
Subtracting y from equation (i)
y + y –y = 2x2 + 4x
x + 2
x2 +5 – [2x2 +5]
y = 4x
x+ 2
2……….(ii)
Dividing ii…………. By x
= 4x +2
x………….iii…
As x
0,
y
0
And
(iii) Becomes
Note: The expression is called derivative of y with respect [w.r.t] to x
The process of finding derivatives is called DIFFERENTIATION.
Example
Differentiate y = x3 +1 with respect to x
Solution
Y +y = [x +
x]3 +1
= x3+ 3x2
x + 3x
x2+
x3+1
Subtracting y
y + y-y = x3+3x2
x+3x
x2+
x3+1 – x3 – 1
y = 3x2
x+3x
x2+
x3
Dividing by x
As x
0,
y
= 3x2
Examples
Find the gradients of the following curves
1.) 2x2-1
2.) y =x3-1
Solution
1) 2x2-1
y+y = 2[x +
x]2-1
y+y =2 [x2+2x
x+
x2]-1
y+y = 2x2 +4x
x+
x2-1…………(i)
Subtracting y from(i)
y + y – y = 2x2 + 4x
x +
x2 – 1 – [ 2x2-1]
y = 2x2+ 4x
x+2
x2-1-2x2+1 ………………..(ii)
Dividing …..(ii) by x
=4x + 2 ………(iii)
As
(iii) Becomes
= 4x
1. y = x3 – 1
Solution
Subtracting y
y + y-y = x3 + 3x 2
+ 3x
x2 +
x3-1-x3 +1
y =3x2
x+ 3x
+
x3
Dividing by
=
= 3x2 + 3x +
x2
As ,
= 3x2
EXERCISE
Find the gradients of the following curves.
1.) y = x2
Solution
y + 2
= x2 + 2x +
x2
Subtracting y
y + y-y= x2 + 2x
+
x2 -x2
y = 2x
+
x2
Dividing by
= 2x +
As
= 2x
2.) y= x3
Solution
y + x = (x +
)3
= x3 + 3x2 + 3x
2 +
x3…….(i)
Subtracting y
y + y-y=X3 + 3x2
x + 3x
x2 +
x3 – x3
y= 3x2
x + 3x
x2 +
x3………….(ii)
Dividing by x
=
= 3x2 + 3xx +
2
As x
0 ,
0 ,
=
x2
3.) y = x
solution
y + x = x +
x………….(i)
subtracting y
y + y-y= x +
x – x
y=
x ………..(ii)
Dividing by x
1
4.) y =3x2
Solution
y + x = 3 [x +
x] 2
=3 [x2+ 2x x +
x2]
=3x2+6x x+3
x2 -3x2……….(i)
Subtracting y
y + y-y= 3x2+6x
x+3
x2-3x2
y= 6x
x+3
x2…….(ii)
Dividing by x
=
As x
0,
y
0,
=
5.) y = x2 +3x
Solution
y +x = [x+
x]2 + 3[x+
x]
x2+2xx+
x2+ 3x+3
x…………i
Subtracting y
y + y-y = X2 + 2x
x+
x2+3x +3
x -(x 2 + 3x)
y = 2x
x +
x2 + 3
x……..ii
Dividing by x
= 2x +x +3
As x →0,
y → 0,
→
2x +3